It's not you : how to identify and heal from narcissistic people / Dr Ramani Durvasula. - Durvasula, Ramani (Vermilion, 2024)
Dealing with a narcissist is hard. One day their confidence and charisma pull you in, the next they gaslight, wreck your self-confidence and leave you wondering what you could have done differently. The answer is: nothing. In 'It's Not You', psychologist and narcissism expert Dr Ramani Durvasula shows how narcissists hijack our wellbeing, and what we can do to break free from toxic relationships and embark on a path towards healing.